PEMANFAATAN MEDIA PEMBELAJARAN INTERAKTIF MELALUI APLIKASI CANVA PADA MATA PELAJARAN SENI BUDAYA DALAM MENINGKATKAN HASIL BELAJAR PADA SISWA KELAS V SD MUHAMMADIYAH 1 LIMBOTO - Veni Susilowati; Herson Anwar; Sabrina Najib mohamad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Education is a conscious effort made by an educator in this era of globalization which is full of challenges to develop and improve the quality of human resources so that they become better at school and outside school. Therefore, education is an option that cannot be ignored by humans, especially in this millennial era, competition will be increasingly tight, intense and fierce to become superior. The aim of this research is to determine the use of learning media, the Canva application or image media, and interest in learning in thematic learning in class V of SD 1 Limboto. The method used is a qualitative descriptive method, the qualitative descriptive method is a research method used to collect and describe data about and information about objects, phenomena and behavior being studied through interview, observation and documentation methods. The use of interactive learning media through the Canva application in thematic learning in the Limboto 1 Elementary School class is quite good. This happens because the elementary school, especially the fifth grade teachers at Limboto 1 Elementary School, are used to implementing thematic learning by using the Canva application, an image media. Of course, this is also supported by complete facilities and infrastructure that are often used by teachers, namely LCD projectors because their benefits are more sophisticated and adaptable to the current digital era. The use of the Canva application can foster students' interest in learning, especially in thematic learning, this can be seen from the enthusiastic attitude of students in learning during learning, students respond actively, both asking and answering teacher questions, students are interested and like learning by using image media, and students do not feel bored, bored and sleepy in learning when using the Canva application learning media or image media